2018
DOI: 10.1097/mao.0000000000001904
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Different Approaches for Clinical Cochlear Coverage Evaluation After Cochlear Implantation

Abstract: Insertion angle measurements are well suited for cochlear coverage determination, especially regarding retrospective analyses. Prospective studies independent of anatomical irregularities should be performed with the newly proposed approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 31 publications
3
24
0
1
Order By: Relevance
“…Therefore, clinical analyses using fpVCT SECO probably represents the true length, since assessments with micro-fpVCT and micro-CT in temporal bone specimens have shown no significant different CDL at the lateral wall values up to over 40 mm [13,24], which corresponds to a CDL OC of about 35 mm. In line with this, in other studies, shorter CDL values have been reported in clinical modalities [8,13]. Based on these and the presented findings, it should be carefully considered whether it might be better to use longer electrodes than currently assumed for covering the correct CDL OC , when measured by MSCT or other low-resolution images.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Therefore, clinical analyses using fpVCT SECO probably represents the true length, since assessments with micro-fpVCT and micro-CT in temporal bone specimens have shown no significant different CDL at the lateral wall values up to over 40 mm [13,24], which corresponds to a CDL OC of about 35 mm. In line with this, in other studies, shorter CDL values have been reported in clinical modalities [8,13]. Based on these and the presented findings, it should be carefully considered whether it might be better to use longer electrodes than currently assumed for covering the correct CDL OC , when measured by MSCT or other low-resolution images.…”
Section: Discussionsupporting
confidence: 84%
“…Therefore, it is necessary to have sufficient data on the cochlear anatomy preoperatively, especially on the cochlear duct length (CDL). In recent years, new imaging technologies, models and formulas have been developed to measure the CDL [5][6][7][8][9][10][11][12][13][14]. Most of these studies were based on measurements of the CDL by Escudé in 2006 [5].…”
Section: Introductionmentioning
confidence: 99%
“…A landmark was finally set every 30° to 60°. 14 , 15 The whole enrolled cochlea is presented by the software in an additional window. Herein, the CDL (A to C) and the 2TL (A to B; Figure 1 , D and D ′ ) were measured in millimeters.…”
Section: Methodsmentioning
confidence: 99%
“…The method of CBCT imaging and analysis and the dataset have been described in detail previously [36][37][38] ; here we reuse these data. In brief, a total of 95 patients (51 female, 44 male) with cochlear implants were included in the analysis.…”
Section: Cbct Measurements ("Clinical Ct")mentioning
confidence: 99%
“…These clinical scans are part of the clinical routine at the Hannover Medical School to preoperatively evaluate the condition of the cochlea and postoperatively confirm correct intracochlear array placement. All segmentations of the cochlear modiolar wall in preoperative CBCT data were performed with the software tool OsiriXMD (version 2.5.1 64bit, Pixmeo SARL, Switzerland) according to previous studies [37][38][39][40] .…”
Section: Cbct Measurements ("Clinical Ct")mentioning
confidence: 99%